Union Territory of Puducherry Draft Annual Plan 2010-11 (Scheduled Caste Sub-Plan - SCSP) - Planning Commission (Planning Commission, 2010)
The Union Territory of Puducherry consists of four regions, namely, Puducherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Puducherry region, which is on the east coast, about 162 kms. south of Chennai is the largest of these and consists of 12 scattered areas interspersed with enclaves of Villupuram district and Cuddalore District of Tamilnadu. Karaikal region is about 150 Kms. south of Puducherry and it is surrounded by Nagapattinam District of Tamilnadu. Yanam region is located about 840 kms. north east of Puducherry near Kakinada in Andhra Pradesh. Mahe region lies almost parallel to Puducherry 653 kms. away on the west coast near Tellicherry in Kerala.
Scheduled Caste Sub-Plan - SCSP
Union Territory of Puducherry